THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. CHAILEASE FINANCE INDONESIA - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2025)
Human resources play a crucial role in a company's success, particularly in facing competition in the globalization era. Enhancing employee performance is one of the primary goals of organizations to achieve optimal productivity. Motivation and work discipline is considered significant factors influence employee performance. This study aims to analyze the effect of motivation and work discipline on employee performance at PT. Chailese Finance Indonesia. The methodology employed includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, as well as t-tests, F-tests, and the coefficient of determination, using data collected through questionnaire from 63 respondents. The results indicate that motivation has a partial effect on employee performance, while work discipline does not mean influence performance. Data analysis was conducted using SPSS 23. These findings provide insights for companies to enhance employee performance through motivational approaches.